Pelatihan Pembuatan Instan Daun Pepaya sebagai ASI Booster - Krisdiana Wijayanti; Murti Ani; Novita Ika Wardani; Aulia Fatmayanti (LPPM Akbid Harapan Ibu Pekalongan, 2020)
The scope of exclusive breastfeeding has not met the set targets. One of the benefits of papaya leaves is ASI Booster (ASI booster), because it can increase milk production and protein levels. The purpose of this community service activity is to improve knowledge and skills about ASI and the technique of instant papaya leaves. The design is the pre test and post test level of knowledge and skills. The material is delivered by lecture and demonstration methods. The evaluation was carried out after the practice of instant making of papaya leaves by carrying out a post test and evaluating the establishment of a banner on the description of instant papaya leaf products and their benefits as ASI smoothers and meeting forums in the village to check information desemination. Community service activities were conducted in 3 meetings. The first meeting was the delivery of material about ASI, ASI smoothing, the benefits of papaya leaves, the technique of instant papaya leaves. The second meeting was the training of instant papaya leaves in the Semarang Department of Health's Health Polytechnic Department, which was attended by 3 cadres of Karangjati Village. The third meeting was carried out to socialize and practice the instant making of papaya leaves in Karangjati Village to the people of Karangjati village. The participants who participated in the community service activities were 30 residents of Karangjati Village, Blora Based on the paired t-test, the Sig. (2-tailed) knowledge of 0,000 (<0,05) and skills of 0,000 (<0,05), then there is the effect of training on instant making of papaya leaves as breast milk booster to the level of knowledge and skills.This community service provides many benefits for participants, namely for cadres and community members. The real form is the increasing knowledge of breast milk and ASI smoothers with the instant making of papaya leaves.